Teenage Pregnancies in Indonesia: Does Socio-Economic Matter? - Masruroh Hasyim; Joko Prasetyo; Agung Dwi Laksono; Nikmatur Rohmah (Universitas STRADA Indonesia, 2025)
Bacground: Teenage pregnancies is a crucial health problem in developing countries, including in Indonesia, which may cause various physical, psychological, emotional, and social problem including death for both mother and baby. Purpose: This current research aimed to analyze the socio-economic relationship with the occurrence of teenage pregnancies in Indonesia. Methods: This study uses secondary data for the 2017 IDHS with cross-sectional design. The dependent variable in this study is the prevalence of pregnant adolescents, while the independent variable is the socioeconomic status, the number of samples in this study was 3350 in women aged 20-24 years. The sampling technique uses simple random sampling. Analysis using binary logistic regression. Results: The results showed that the poorer women had 0.804 times the probability of having teenage pregnancies (AOR 0.804; 95% CI 0.655-0.986). The women with middle socio-economic have 0.640 times more chance than the most impoverished women to have teenage pregnancies (AOR 0.640; 95% CI 0.514-0.797). The wealthier women have 0.804 times the probability of having teenage pregnancies compared to the poorest women (AOR 0.804; 95% CI 0.655-0.986). Moreover, the wealthiest women are 0.607 times more likely than the poorest women to have teenage pregnancies (AOR 0.607; 95% CI 0.447-0.823). Conclusion: The study concluded that socio-economic proved to be related to the occurrence of teenage pregnancies in Indonesia. Also, there are 3 other variables which are also significant predictors of teenage pregnancy. The three variables are age, education level, and employment status.